Solving bi-objective unconstrained binary quadratic programming problem with multi-objective path relinking algorithm - Lei Song; Rong-Qiang Zeng; Yang Wang; Ming-Sheng Shang (2016 12th International Conference on Natural Computation, Fuzzy Systems and Knowledge Discovery (ICNC-FSKD), 2016)
This paper investigates a multi-objective path relinking algorithm in order to optimize a bi-objective unconstrained binary quadratic programming problem. In this algorithm, we integrate the path relinking techniques into hypervolume-based multi-objective optimization, where we propose a method to generate a path and select a set of non-dominated solutions from the generated path for further improvements. Experimental results show that the proposed algorithm is very effective compared with the original multi-objective optimization algorithms.